Buku Muhammad His Life Based on The Earliest Sources Karya Martin Lings: Sebuah Kajian Historiografi - Muhammad Irham; Agus Permana (Historia Madania: Jurnal Ilmu Sejarah, 2019)
The book of “Muhammad: His Life Based on Earliest Sources” was written by Martin Lings, who after converting to Islam got the name Abu Bakar Sirajuddin. Since it was first published in 1983, this book has received many awards and has been translated into 10 languages. This book discusses the biography of the Prophet Muhammad and uses classical sources that are so authoritative from the 2nd century D / 8 M and 3 D / 9 M. This research aims to find out the life history and work of Martin Lings, the contents of the book Muhammad His Life based on the Earliest Sources, and their historiographic analysis. The method used is a historical research method which consists of four stages, namely heuristics (collection of sources), criticism (selection of sources), interpretation (interpretation of data), and historiography (writing of history). Based on research that has been done, it is known that Martin Lings came from England and in 1938 he converted to Islam. He died in 2005 in England. Muhammad's book: His Life Based on Earliest Sources, written by Martin Lings, first published in 1983. This book is divided into 85 parts which can be collected into 4 groups, namely before the birth of the Prophet Muhammad, the life of the Prophet Muhammad in Mecca, the life of the Prophet Muhammad in Medina and Islamic themes. In it, Lings selects the source he uses so he only chooses the earliest source. The style of writing Muhammad His Life's book based on the Earliest Sources by Martin Lings is a type of Sirah included in the biographical tradition in Muslim historiography. The uniqueness that is contained in this book is; the author is a convert to Islam and Sufi, uses authentic sources, written in literary language, and combines socio-cultural analysis with the reading of scriptures and hadith, and also includes stories of miracles.